Family ownership concentration and real earnings management: Empirical evidence from an emerging market - Belal Ali Abdulraheem Ghaleb; Hasnah Kamardin; Mosab I. Tabash (Cogent Economics & Finance, 2020)
The paper examines the effect of family ownership concentration (FMOC) on real earnings management (REM) in manufacturing firms listed on Bursa Malaysia (formerly known as Kuala Lumpur Stock Exchange). Data are gathered from 1,056 firm-year observations for the four-year period from 2013 to 2016. The feasible generalised least square estimation is used to examine the relationships. The results show that FMOC is negatively and significantly associated with REM. This evidence supports the alignment hypothesis that FMOC mitigates managerial earnings management by preventing real activities manipulation. However, the finding of the current study is contrary to the claim that family-controlled firms have lower earnings quality. This study extends previous empirical research by examining the effect of different levels of family control on REM in an emerging market and provides evidence that family firms have less incentive to engage in REM practices. The findings imply that earnings reported in the financial statements of Malaysian manufacturing family firms are more reliable as these firms do not manipulate earnings through real business activities. Policymakers may consider the results of the current study that show family-controlled firms have the motivation to self-monitor their business and avoid earnings manipulation activities. Investors may benefit from this evidence and invest in family firms. Future studies may extend the sample to cover other sectors to check the consistency of the findings. In addition, the paper uses data from Malaysia, a country characterised as a family-controlled market. Thus, the findings may not be similar to those of countries with lower FMOC.
Keywords: 330; family ownership concentration; family-controlled firms; real earnings management; alignment hypothesis; emerging market